Laser-induced graphene electrode based on solid ionic liquid, preparation method and application

By modifying PEDOT:PSS film layer and bimetallic nanocomposite on the working electrode surface of the gas sensor, and drip casting of solid ionic liquid layers in the sensing area, the existing gas sensors are solved inadequate sensitivity when detecting low concentrations of toxic and harmful gases and The problem of liquid electrolyte leakage achieves higher detection performance and stability.

CN118795004BActive Publication Date: 2025-02-07ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411285083.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-02-07
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing gas sensors have insufficient sensitivity when detecting low concentrations of toxic and harmful gases, and liquid electrolytes are prone to leaking, reducing the stability of the sensor.

Method used

Using a laser-induced graphene electrode based on solid ionic liquid, the PEDOT:PSS film layer and bimetallic nanocomposite are modified on the surface of the working electrode to increase the active site and catalytic activity, and the solid ionic liquid layer is dripped into the sensing area. Form an electrochemical gas sensor.

Benefits of technology

It significantly improves gas detection performance, avoids leakage of liquid electrolytes, enhances the stability and life of the sensor, and improves sensitivity and detection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118795004B_ABST
    Figure CN118795004B_ABST
Patent Text Reader

Abstract

The present invention discloses a laser-induced graphene electrode based on solid ionic liquid, a preparation method and an application. The present invention adopts laser-induced graphene technology to carve a graphene interdigitated three-electrode on the surface of a polyimide tape, and uses a solid ionic liquid as an electrolyte. The solid ionic liquid can ensure that the electrolyte has a long life, so that the gas sensor has good time stability. A PEDOT:PSS film layer and a bimetallic nanocomposite are modified on the surface of the working electrode to amplify the gas response signal. The present invention uses laser-induced graphene technology, which is convenient and fast to process, low in cost, can achieve large-scale preparation in a short time, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas sensors and chemical sensors, and in particular to a laser-induced graphene electrode based on solid ionic liquid, a preparation method and an application thereof. Background Art

[0002] In daily life, toxic and harmful gas leakage may occur in the process of industrial and agricultural production. If not discovered and handled in time, it may lead to serious consequences such as poisoning or explosion, posing a serious threat to people's life, health and property safety. Therefore, it is necessary to detect the leakage of toxic and harmful gases in a timely manner, which is crucial for safety warning and people's life safety protection.

[0003] At present, there are many methods for the detection of toxic and harmful gases, including gas chromatography-mass spectroscopy (GC-MS), spectroscopy, conductivity and electrochemical methods. The GC-MS method has extremely high sensitivity and accuracy, but the equipment is bulky, expensive, complicated to operate, and requires specialized technicians; the spectroscopy method realizes quantitative detection through the absorption of specific wavelength spectra by gases, and has the characteristics of high sensitivity and high selectivity, but it needs to be equipped with complex equipment such as light sources, optical components and detectors. The configuration and maintenance costs of the equipment are high, and high power consumption is required, which poses a challenge to the use and durability of the equipment; the conductivity method usually uses metal oxide semiconductors as sensitive elements. According to the interaction between gas and oxide surface, redox reaction will occur, thereby changing the conductive properties of the material, and finally detecting gas concentration by measuring the change in resistance, but this type of sensor has poor selectivity and high operating temperature. Compared with the previous methods, the electrochemical method has excellent sensitivity and specificity, is easy to miniaturize, and is very suitable for the detection of toxic and harmful gases.

[0004] Electrochemical sensors are usually manufactured using micro-nano processing technology, which is expensive, cumbersome to operate, and high in cost. The detection target of low concentrations of toxic and harmful gases requires the sensor to have higher sensitivity. Electrochemical sensors work in an environment that supports electrolytes. The room temperature ionic liquids commonly used as electrolytes have the advantages of a wide electrochemical window and are not easily volatile, but the flowable state of the liquid is prone to electrolyte leakage, which also reduces the stability of the sensor. Summary of the invention

[0005] The purpose of the present invention is to provide a laser-induced graphene electrode based on solid ionic liquid, a preparation method and application thereof in view of the deficiencies of existing gas sensors.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a laser-induced graphene electrode based on solid ionic liquid, comprising a flexible substrate, a polyimide tape attached to the flexible substrate, a working electrode, a reference electrode, a counter electrode, a silver / silver chloride paste layer coated on the reference electrode, a PEDOT:PSS film layer and a bimetallic nanocomposite modified on the surface of the working electrode, a solid ionic liquid layer, a silver conductive region formed by coating a conductive silver paste, and an insulating layer;

[0008] The working electrode, the reference electrode and the counter electrode constitute a graphene interdigitated three-electrode, which is prepared by laser-induced graphene technology;

[0009] The insulating layer is coated on the non-sensing area so that the laser-induced graphene electrode only exposes the sensing area required for gas detection. A layer of solid ionic liquid is drop-cast on the sensing area as an electrolyte to form an electrochemical gas sensor to achieve rapid and highly sensitive sensing of gas.

[0010] Furthermore, the preparation process of the graphene interdigitated three-electrode is: sticking a polyimide tape evenly to the surface of a flexible substrate, and engraving the interdigitated three-electrode on the surface of the polyimide tape with a carbon dioxide laser engraving machine at a suitable power.

[0011] Furthermore, a PEDOT:PSS thin film layer is modified on the surface of the working electrode by a constant voltage deposition method to increase the active area of ​​the working electrode and amplify the gas response signal.

[0012] Furthermore, the bimetallic nanocomposite is modified on the surface of the working electrode by a constant voltage deposition method, and the response characteristics and detection performance of the gas sensor are improved by the synergistic effect of the bimetallic nanocomposite.

[0013] Furthermore, the bimetallic nanocomposite includes a gold-platinum nanocomposite and a platinum-palladium nanocomposite.

[0014] Furthermore, the solid ionic liquid layer is composed of polyvinylidene fluoride and 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, and the preparation process is: first dissolve polyvinylidene fluoride in N,N-dimethylformamide, then add 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide and mix evenly, and then drop-cast it on the sensing area, and form a solid ionic liquid layer after the residual N,N-dimethylformamide evaporates.

[0015] Furthermore, when preparing the solid ionic liquid layer, carbon nanotubes are doped to improve the conductivity of the solid ionic liquid. The preparation process is: first, the carbon nanotubes are evenly mixed with 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, and then mixed with an N,N-dimethylformamide solution of polyvinylidene fluoride, and then drop-casted on the sensing area, and the solid ionic liquid layer is formed after the residual N,N-dimethylformamide evaporates.

[0016] Furthermore, when preparing the solid ionic liquid layer, gold nanoparticles are doped to improve the conductivity of the solid ionic liquid. The preparation process is: dissolving gold nanoparticles in water to form a nanogold solution, mixing the nanogold solution with an N,N-dimethylformamide solution, and then adding polyvinylidene fluoride. After complete dissolution, 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide is added and mixed evenly, and finally drop-casting is performed on the sensing area to form a solid ionic liquid layer after the residual N,N-dimethylformamide is volatilized.

[0017] Furthermore, the flexible substrate material is polyethylene terephthalate, with a thickness of 0.3-0.8 mm, and can be bent; the polyimide tape has a thickness of 0.05-0.1 mm.

[0018] Furthermore, the thickness of the graphene interdigitated three-electrode is 40-50 μm.

[0019] In a second aspect, the present invention provides a method for preparing a laser-induced graphene electrode based on a solid ionic liquid, the method comprising the following steps:

[0020] (1) A polyimide tape is pasted on the surface of a flexible substrate to form a base, and after the base is cleaned and blown dry, a carbon dioxide laser engraving machine is used to batch engrave the drawn interdigitated three-electrode pattern on the surface of the polyimide tape;

[0021] (2) The engraved interdigitated three-electrode was cleaned and dried, and then connected to an electrochemical workstation. An external silver / silver chloride reference electrode and a platinum counter electrode were used to perform electroplating in an EDOT:PSS solution at a positive voltage to form a PEDOT:PSS thin film layer on the surface of the working electrode. After cleaning and drying again, an external silver / silver chloride reference electrode and a platinum counter electrode were used to prepare a bimetallic nanocomposite by electroplating on the surface of the working electrode at a negative voltage.

[0022] (3) After cleaning and drying the modified interdigitated three-electrode, silver / silver chloride paste is coated on the reference electrode area to form a silver / silver chloride paste layer, and then UV glue is coated on the non-sensing area to prepare an insulating layer. After curing the UV glue, conductive silver paste is coated on the ends of the three electrodes to form a silver conductive area;

[0023] (4) The solid ionic liquid is first placed in an oven to make it flowable, then drop-cast on the sensing area, scraped flat and dried, and a solid ionic liquid layer is formed after the residual N,N-dimethylformamide evaporates.

[0024] In the third aspect, the present invention provides an application of a laser-induced graphene electrode based on solid ionic liquid in electrochemical gas sensing. According to the oxidation potential of the gas to be detected, a voltage is applied to the working electrode, and the gas response signal is detected using the chronoamperometry method. Quantitative gas detection is achieved through the gas response signal.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention modifies the surface of the working electrode with a PEDOT:PSS thin film layer and a bimetallic nanocomposite to increase active sites and catalytic activity, thereby significantly improving gas detection performance.

[0027] 2. The present invention uses solid ionic liquids, which have the characteristics of low volatility, wide potential window, and small volume compared to typical gas sensors that use aqueous solutions such as potassium chloride as electrolytes. Compared with room temperature ionic liquids, the present invention avoids the problem of ionic liquid leakage, increases electrode life, and enhances time stability.

[0028] 3. The present invention dopes carbon nanotubes or gold nanoparticles into the solid ionic liquid, which can significantly improve the conductivity of the solid ionic liquid and help further improve the sensing performance.

[0029] 4. The present invention uses laser-induced graphene technology in the electrode preparation process, which is suitable for mass production, low cost, convenient and fast preparation, and has good application prospects.

[0030] 5. The present invention uses a flexible substrate, which is easy to bend and is suitable for flexible gas sensors and wearable detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic structural diagram of a laser-induced graphene electrode based on solid ionic liquid provided in an embodiment of the present invention;

[0032] Figure 2 is a schematic diagram of a laser-induced graphene electrode based on solid ionic liquid for gas sensing provided by an embodiment of the present invention;

[0033] Figure 3 This is a scanning electron microscope characterization result diagram of a laser-induced graphene electrode based on a solid ionic liquid provided in an embodiment of the present invention;

[0034] Figure 4This is a Raman spectrum characterization result diagram of a laser-induced graphene electrode based on a solid ionic liquid provided in an embodiment of the present invention;

[0035] Figure 5 This is a result diagram of the laser-induced graphene electrode based on solid ionic liquid provided in an embodiment of the present invention detecting methane gas with a concentration of 10ppm-600ppm;

[0036] Figure 6 It is a linear fitting diagram of the results of detecting methane gas with a concentration of 10ppm-600ppm by the laser-induced graphene electrode based on solid ionic liquid provided in an embodiment of the present invention;

[0037] Figure 7 This is a result diagram of repeated detection of 50 ppm methane by a laser-induced graphene electrode based on solid ionic liquid provided by an embodiment of the present invention;

[0038] In the figure, flexible substrate 1, polyimide tape 2, silver conductive area 3, insulating layer 4, counter electrode 5, working electrode 6, reference electrode 7, silver / silver chloride paste layer 8, PEDOT:PSS film layer 9, bimetallic nanocomposite 10, solid ionic liquid layer 11, air chamber 12, air inlet 12.1, air outlet 12.2, PCB board 13, and pad 14. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0040] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0042] The embodiments of the present invention firstly introduce in detail the working principle of the laser induced graphene electrode of the present invention for high-sensitivity gas detection.

[0043] Gas sensors are usually composed of a working electrode, a counter electrode, a reference electrode and an electrolyte, wherein the working electrode detects the target gas by applying a voltage. The PEDOT:PSS thin film layer and the bimetallic nanocomposite modified on the surface of the working electrode in the present invention can further improve the detection effect of the sensor by increasing the active sites and catalytic activity. The counter electrode is used to form a current loop with the working electrode, and the reference electrode is used to provide a stable reference potential. The electrolyte is used to achieve ion conduction, and aqueous solutions such as sulfuric acid and potassium chloride are usually used. The present invention uses solid ionic liquids, which have the advantages of being difficult to volatilize, having a long life, good conductivity, a wide potential window, and easy integration, while avoiding the leakage problem that may occur in liquid ionic liquids. Some electrochemically active gases, such as oxygen, hydrogen, nitric oxide, sulfur dioxide and other gases, when an external voltage is applied to the working electrode, the gas will undergo an oxidation-reduction reaction on the electrode surface, resulting in the gain and loss of electrons, thereby forming a response current between the working electrode and the counter electrode. The magnitude of the response current is linearly related to the concentration of the target gas, so the quantitative detection of the target gas can be achieved by detecting the magnitude of the response current.

[0044] The detailed structure of a laser-induced graphene electrode based on solid ionic liquid proposed in the embodiment of the present invention will be combined with Figure 1 The laser induced graphene electrode mainly includes a flexible substrate 1, a polyimide tape 2 pasted on the flexible substrate, a working electrode 6, a reference electrode 7, a counter electrode 5, a silver / silver chloride paste layer 8 coated on the reference electrode, a PEDOT:PSS film layer 9 and a bimetallic nanocomposite 10 modified on the surface of the working electrode for amplifying the response signal, a solid ionic liquid layer 11, a silver conductive area 3 formed by coating a conductive silver paste, and an insulating layer 4. Among them, the working electrode 6, the reference electrode 7 and the counter electrode 5 constitute a graphene interdigitated three-electrode, which is prepared by laser induced graphene technology.

[0045] Furthermore, in the present embodiment, the flexible substrate 1 adopts a flexible polyethylene terephthalate (PET) substrate, the thickness of the flexible substrate 1 is 0.3-0.8mm, easy to bend, and the thickness of the polyimide tape 2 pasted on its surface is 0.05-0.1mm. A carbon dioxide laser engraving machine is used to engrave a laser-induced graphene fork-finger three-electrode on the surface of the polyimide tape 2. Since the laser is focused on the surface of the polyimide to produce a photothermal effect, the local temperature rises instantly, and the formation of laser-induced graphene is accompanied by the release of gas products, thereby forming a porous fluffy structure, which is more suitable for gas detection. The working electrode 6 and the counter electrode 5 are fork-finger structures, and the fork spacing and fork width are equal, with a total of four pairs of forks. When using a carbon dioxide laser engraving machine, the engraved pattern is drawn using CorelDRAW2019 software, and the electrode array can be drawn in one picture, thereby realizing batch engraving and improving the preparation efficiency of laser-induced graphene electrodes. The flexible substrate 1 with a thickness of 0.3-0.8 mm is very easy to cut. After the electrode array is engraved, the electrodes are cut one by one. The surface of the reference electrode 7 is coated with a silver / silver chloride paste layer 8 for stabilizing the potential. The silver / silver chloride paste layer 8 can be composed of silver, silver chloride and an adhesive. The PEDOT:PSS film layer 9 and the bimetallic nanocomposite 10 are modified on the surface of the working electrode 6 by electroplating.

[0046] Furthermore, the solid ionic liquid layer 11 is composed of polyvinylidene fluoride PVDF and 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide. The specific preparation process is: first dissolve PVDF in N,N-dimethylformamide DMF, then add 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, mix well, put in a 60-80℃ oven, then drop cast 5-10μL on the sensing area, scrape flat, bake under infrared lamp overnight, and form the solid ionic liquid layer 11 after DMF is completely volatilized.

[0047] Furthermore, when preparing the solid ionic liquid layer 11 , carbon nanotubes or gold nanoparticles may be doped to improve the conductivity of the solid ionic liquid.

[0048] Solid ionic liquid doped carbon nanotubes are firstly mixed with 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, then mixed with PVDF DMF solution, and then drop-casted on the sensing area to form a solid ionic liquid layer after the residual DMF evaporates.

[0049] Solid ionic liquid doped gold nanoparticles are prepared by first dissolving the gold nanoparticles in water to form a nanogold solution, then mixing the nanogold solution with a DMF solution, and then adding PVDF. After the solution is completely dissolved, 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide is added and mixed evenly, and finally drop-casting is performed on the sensing area to form a solid ionic liquid layer after the residual DMF evaporates.

[0050] Furthermore, the silver conductive area 3 is to apply the conductive silver paste to the ends of the three electrodes with a brush pen for subsequent gas detection. The insulating layer 4 is coated with UV glue on the non-sensing area and then quickly cured under ultraviolet light, so that each laser-induced graphene electrode exposes the same sensing area, improving the consistency of electrode sensing.

[0051] In the following examples, the preparation method of laser-induced graphene electrode based on solid ionic liquid is described in detail:

[0052] (1) Use CorelDRAW2019 software to draw the interdigitated three-electrode array pattern. The interdigital spacing and interdigital width are both 400μm, the interdigital length is 8mm, and there are four pairs of interdigits. A polyimide tape 2 with a thickness of 0.055mm is pasted on the surface of a flexible PET substrate with a thickness of 0.5mm to form a substrate. The surface of the polyimide tape is cleaned with water, ethanol, and water in turn to remove surface impurities. The substrate is then blown dry with a nitrogen gun. A carbon dioxide laser engraving machine is used to batch engrave on the surface of the polyimide tape 2 according to the pattern drawn in advance. The power is 9.5W and the step speed is 55mm / min. Because the laser is focused on the polyimide surface to produce photothermal effect, the local temperature rises instantly, and the formation of laser-induced graphene is accompanied by the release of gas products, thereby forming a porous and fluffy structure on the electrode surface, such as Figure 3 As shown. Raman spectroscopy was performed on the laser-induced graphene electrode, and the results are shown Figure 4 As shown, three characteristic peaks can be seen, proving that a graphene structure has been formed;

[0053] (2) The engraved interdigitated three-electrode was washed with water, ethanol, and water in turn, dried under an infrared lamp, and then connected to an electrochemical workstation. An external silver / silver chloride reference electrode and a platinum counter electrode were used for electroplating in a 0.02 M EDOT / 1% PSS solution at a voltage of 0.9 V for 150 s to form a PEDOT:PSS thin film layer on the surface of the working electrode by electropolymerization 9;

[0054] (3) After cleaning and drying the interdigitated three-electrode, an external silver / silver chloride reference electrode and a platinum counter electrode were used again, and the electrode sensing area was immersed in a 5 mM chloroauric acid / 0.5 M sulfuric acid solution, and electroplated at a voltage of -0.1 V for 300 s, and then in a 5 mM potassium chloroplatinate solution / 0.5 M sulfuric acid solution, and electroplated at a voltage of -0.3 V for 300 s to prepare a gold-platinum bimetallic nanocomposite on the surface of the working electrode;

[0055] (4) After the modified interdigitated three-electrode is cleaned and dried under an infrared lamp, a silver / silver chloride paste is coated on the reference electrode area to stabilize the potential, and dried under an infrared lamp to form a silver / silver chloride paste layer 8;

[0056] (5) Coating the non-sensing area with UV glue to expose the sensing area of ​​a fixed area, preparing an insulating layer 4, irradiating under ultraviolet light to cure the UV glue, and coating the ends of the counter electrode 5, the working electrode 6 and the reference electrode 7 with conductive silver paste to form a silver conductive area 3, which is convenient for subsequent gas detection lead connection;

[0057] (6) Mix 3 mg of carbon nanotubes with 1 g of 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide, and sonicate for 1 hour to mix them evenly. Add 0.5 g of PVDF to 3 g of DMF solution, and sonicate for 1 hour to dissolve PVDF in the DMF solution. Then add the mixed solution of carbon nanotubes and 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide to the DMF mixed solution of PVDF, mix evenly, and place in a 70°C oven for 2 hours. Drop cast 10uL of the mixed solution on the sensing area, scrape it as flat as possible, and then place it under an infrared lamp to dry overnight. After the residual DMF evaporates completely, a solid ionic liquid layer 11 doped with carbon nanotubes is formed;

[0058] The specific process for preparing the solid ionic liquid layer doped with gold nanoparticles is as follows: 300 μL of nanogold solution is mixed with 3 g of DMF solution, and the mixture is uniformly mixed by ultrasonication for 10 min, and then 0.5 g of PVDF is added, and the mixture is completely dissolved by ultrasonication for 1 h. Finally, 1 g of 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide is added. After mixing evenly, the mixture is placed in an oven at 70°C for 2 h. 10 uL of the mixed solution is drop-casted on the sensing area, and it is scraped as flat as possible, and then dried under an infrared lamp overnight. After the residual DMF and water are completely evaporated, a solid ionic liquid layer 11 doped with gold nanoparticles is formed.

[0059] The prepared laser-induced graphene electrode based on solid ionic liquid is applied to electrochemical gas sensing. When performing electrochemical gas detection, the laser-induced graphene electrode needs to be pasted to a PCB board 13 and covered with a gas chamber 12, such as Figure 2As shown. The pad 14 is located at the position corresponding to the three interdigitated electrodes, and the silver conductive area 3 is connected to the pad 14 by conductive silver paste. To prevent air leakage, the connection between the air chamber 12 and the PCB board 13 is sealed with hot melt adhesive. The gas to be detected is introduced from the air inlet 12.1 of the air chamber 12, passes through the sensing area of ​​the laser-induced graphene electrode, and is discharged from the air outlet 12.2.

[0060] Taking methane detection as an example, according to the oxidation potential of methane, a voltage of 1V is applied to the working electrode 6, and methane reacts with oxygen to generate carbon dioxide and water. The methane gas response signal is detected using the chronoamperometry method. The modified PEDOT:PSS film layer 9 and the bimetallic nanocomposite 10 on the working electrode 6 have the effect of increasing electrochemical active sites and catalytic performance, which can significantly amplify the methane gas response signal and achieve high sensitivity and low detection limit of methane gas sensing. The results are shown in FIG. Figure 5 shown. Figure 5 The concentration gradient of methane in the water was set to 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600 ppm. Figure 5 It can be seen that for 10 ppm of methane, the laser-induced graphene electrode also has a relatively obvious response, indicating that the electrode designed in the present invention has a lower detection limit. Figure 5 Linear fitting is performed on the results of methane gas responses at different concentrations. The fitting results are shown in Figure 6 As shown, R 2 is an indicator of the degree of fit of the trend line, and its size reflects the degree of fit between the estimated value of the trend line and the corresponding actual data; X and Y represent the methane concentration and the current size respectively. It can be seen from the figure that the linearity is good. The repeatability of the electrode was further tested by repeatedly measuring 50ppm of methane. The results are as follows Figure 7 As shown, the repeatability of the electrodes is good.

[0061] The above description is merely a preferred embodiment of one or more embodiments of the present specification and is not intended to limit one or more embodiments of the present specification. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present specification shall be included in the scope of protection of one or more embodiments of the present specification.

Claims

1. A laser-induced graphene electrode based on solid ionic liquid, characterized in that: It comprises a flexible substrate, a polyimide tape attached to the flexible substrate, a working electrode, a reference electrode, a counter electrode, a silver / silver chloride paste layer coated on the reference electrode, a PEDOT:PSS film layer and a bimetallic nanocomposite modified on the surface of the working electrode, a solid ionic liquid layer, a silver conductive region formed by coating a conductive silver paste, and an insulating layer; The working electrode, the reference electrode and the counter electrode constitute a graphene interdigitated three-electrode, which is prepared by laser-induced graphene technology; The PEDOT:PSS thin film layer is modified on the surface of the working electrode by constant voltage deposition method to increase the active area of ​​the working electrode and amplify the gas response signal, specifically: the interdigitated three-electrode is connected to the electrochemical workstation, an external silver / silver chloride reference electrode and a platinum counter electrode are used, and electroplating is performed at a voltage of 0.9V for 150s in a 0.02M EDOT / 1%PSS solution to form a PEDOT:PSS thin film layer on the surface of the working electrode by electropolymerization; The bimetallic nanocomposite is modified on the surface of the working electrode by a constant voltage deposition method, and the response characteristics and detection performance of the gas sensor are improved by the synergistic effect of the bimetallic nanocomposite; The insulating layer is coated on the non-sensing area, so that the laser-induced graphene electrode only exposes the sensing area required for gas detection, and a layer of solid ionic liquid is drop-casted in the sensing area as an electrolyte; The solid ionic liquid layer is composed of polyvinylidene fluoride and 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, and the preparation process is as follows: firstly, polyvinylidene fluoride is dissolved in N,N-dimethylformamide, then 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide is added and mixed evenly, and then drop-casted on the sensing area, and the residual N,N-dimethylformamide is volatilized to form a solid ionic liquid layer; When preparing the solid ionic liquid layer, carbon nanotubes are doped to improve the conductivity of the solid ionic liquid. The preparation process is: first, the carbon nanotubes are evenly mixed with 1-n-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, then mixed with a polyvinylidene fluoride N,N-dimethylformamide solution, and then drop-casted on the sensing area, and the solid ionic liquid layer is formed after the residual N,N-dimethylformamide is volatilized; or, Gold nanoparticles are doped to improve the conductivity of solid ionic liquids. The preparation process is as follows: gold nanoparticles are dissolved in water to form a nanogold solution, the nanogold solution is mixed with an N,N-dimethylformamide solution, and polyvinylidene fluoride is added. After polyvinylidene fluoride is completely dissolved, 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide is added and mixed evenly, and finally drop-casted on the sensing area to form a solid ionic liquid layer after the residual N,N-dimethylformamide evaporates.

2. The laser-induced graphene electrode based on solid ionic liquid according to claim 1, characterized in that: The preparation process of the graphene interdigitated three-electrode is as follows: a polyimide tape is evenly attached to the surface of a flexible substrate, and a carbon dioxide laser engraving machine is used to engrave the interdigitated three-electrode on the surface of the polyimide tape.

3. The laser-induced graphene electrode based on solid ionic liquid according to claim 1, characterized in that: The bimetallic nanocomposite comprises a gold-platinum nanocomposite and a platinum-palladium nanocomposite.

4. A method for preparing a laser-induced graphene electrode according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) A polyimide tape is pasted on the surface of a flexible substrate to form a base, and after the base is cleaned and blown dry, a carbon dioxide laser engraving machine is used to batch engrave the drawn interdigitated three-electrode pattern on the surface of the polyimide tape; (2) The engraved interdigitated three-electrode was cleaned and dried, and then connected to an electrochemical workstation. An external silver / silver chloride reference electrode and a platinum counter electrode were used to electroplate in a 0.02M EDOT / 1%PSS solution at a voltage of 0.9V for 150s to form a PEDOT:PSS thin film layer on the surface of the working electrode. After cleaning and drying again, an external silver / silver chloride reference electrode and a platinum counter electrode were used to prepare a bimetallic nanocomposite by electroplating on the surface of the working electrode at a negative voltage; (3) After cleaning and drying the modified interdigitated three-electrode, silver / silver chloride paste is coated on the reference electrode area to form a silver / silver chloride paste layer, and then UV glue is coated on the non-sensing area to prepare an insulating layer. After curing the UV glue, conductive silver paste is coated on the ends of the three electrodes to form a silver conductive area; (4) The solid ionic liquid is first placed in an oven to make it flowable, then drop-cast on the sensing area, scraped flat and dried, and a solid ionic liquid layer is formed after the residual N,N-dimethylformamide evaporates.

5. Application of the laser induced graphene electrode according to any one of claims 1 to 3 in electrochemical gas sensing, characterized in that: According to the oxidation potential of the gas to be detected, a voltage is applied to the working electrode, and the gas response signal is detected using the chronoamperometry method, and quantitative gas detection is achieved through the gas response signal.

Citation Information

Patent Citations

  • Micro-cavity integrated electronic nose and application thereof in volatile gas sensing

    CN115575462A

  • Electrochemical chlorine gas sensor and fabrication thereof

    US20170299542A1

  • Gas sensor and method of making the same

    US20200064292A1